Process evaluation of a systemic intervention to identify and support partner violence survivors in a multi-specialty health system - Emma C. Jackson; Lynette M. Renner; Nyla I. Flowers; Mary E. Logeais; Cari Jo Clark (BMC, 2020)
Abstract Background Intimate partner violence (IPV) is highly prevalent in the United States and impacts the physical and mental health and social well-being of those who experience it. Healthcare settings are important intervention points for IPV screening and referral, yet there is a wide range of implementation of IPV protocols in healthcare settings in the U.S., and the evidence of the usefulness of IPV screening is mixed. This process evaluation investigates the facilitators and barriers to implementing Coordinated Care for IPV Survivors through the M Health Community Network ("M Health Network"), an intervention that aimed to standardize IPV screening and referral in a multi-specialty clinic and surgery center (CSC). Two validated IPV screens were introduced and mandated to be done by rooming staff at least once every 3 months with all clinic patients regardless of gender; the Humiliation Afraid Rape Kick (HARK) for presence of IPV and the shortened Danger Assessment (DA-5) for lethality of IPV. Upon a positive screen, the patient was offered immediate informational resources and, if willing, was referred to a social worker for care coordination with a community organization. Methods Semi-structured, individual and group process interviews with clinic managers and clinic staff at 8 CSC clinics (N = 24) were undertaken at 3,12, and 27 months after intervention start. Semi-structured interviews were undertaken with the research team (N = 3) post-implementation. A Consolidated Framework for Implementation Research (CFIR) codebook was used to code data in two rounds. After each round, thick description was used to write detailed and contextual descriptions of each code. Facilitators and barriers to implementation were identified during the second round of thick description. Results Facilitators to implementation were clinic staff support, dedication, and flexibility and research team engagement. Barriers were lack of prioritization, loss of intervention champions, lack of knowledge about intervention protocol and resources, staff and patient discomfort discussing IPV, and operational issues with screen technology. Conclusions The IPV protocol was implemented, but faced common barriers. CFIR is a complex, but comprehensive, tool to guide process evaluation for IPV screening and referral interventions in health systems in the U.S.